THE ROLE OF GOLKAR INSTITUTE IN STRENGTHENING THE COMMITMENT OF YOUNG CADRES OF THE GOLONGAN KARYA POLITICAL PARTY IN THE REGIONAL POLITICAL ARENA - Muhammad Kholid Syaifullah; Jamil; Endang Herliah; Wingkolatin; Jawatir Pardosi; Asnar (SOSIOEDUKASI, 2025)
Muhammad Kholid Syaifullah, Faculty of Teacher Training and Education, Mulawarman University. The Role of Golkar Institute in Strengthening the Commitment of Young Cadres of the Golkar Party in Regional Politics. under the guidance of Dr. Jamil., S.Pd., MAP as Supervisor I and Mrs. Endang Herliah., S.Pd., M.Pd as Supervisor II. The purpose of this study is to analyze the role of the Golkar Institute and the obstacles encountered by the Golkar Institute in strengthening the commitment of young cadres, identifying solutions through programs and activities outlined in the work program and measuring the impact of the program on young cadres in contesting in the regional political arena.This type of research is descriptive qualitative. This research was conducted from August to October 2024. The subjects of this research were the Chairman of the Board of Directors, Academic Manager, and several alumni of the Golkar Institute who are dynamic in regional politics. Data collection techniques used observation, interviews, and documentation. Data analysis techniques used the Miles and Huberman model. Data validity used data triangulation. The results of the study show that the growth of commitment and awareness of dynamics in the regional political arena is supported by the quality and capabilities of young cadres. Golkar Institute as an educational and training institution has a great responsibility in providing knowledge and skills. Various obstacles both internally and externally are faced with various optimizations of work programs such as training, Executive Education Program For Young Political Leaders and so on. These various efforts are made to prepare quality cadres who are ready to serve in the region through direct contributions.